Association between Mindful Eating and Food Consumption in the NutriNet-Santé Cohort Study - Pauline Paolassini-Guesnier; Marion Van Beekum; Rebecca Shankland; Angélique Rodhain; Emmanuelle Kesse-Guyot; Mathilde Touvier; Sandrine Péneau (Proceedings)
Background and objectives: Mindful eating (ME) is defined as non-judgmental awareness of the physical and emotional sensations experienced while eating. An association between ME and healthier eating behaviors has been suggested. However, there are only few observational studies available. The aim of this cross-sectional study was to investigate the association between ME levels and food consumption, in particular, diet quality, food groups, and ultra-processed food consumption, in a general population sample. Methods: In 2022, 2069 participants of the NutriNet-Santé Study completed the Mind-Eat scale, a validated questionnaire assessing ME as a whole and its six dimensions. Participants also completed at least three 24 h dietary records. Adherence to the French dietary guidelines was assessed via the French National Nutrition and Health Program Guideline Score (PNNS-GS2). The degree of food processing was assessed using the NOVA classification. Logistic and linear regressions were used to analyze associations between ME as the exposure (score from 1 to 5), and diet quality, food groups, and ultra-processed food consumption as outcomes, stratified by sex, and considering sociodemographic and lifestyle covariates. Results: Men and women with a higher ME score showed better adherence to dietary guidelines (men: β = 1.05, 95%CI: 0.53, 1.58; women: β = 0.74, 95%CI: 0.40, 1.09), and a lower consumption of ultra-processed food (men: β = −0.02, 95%CI: −0.04, −0.01; women: β = −0.02, 95%CI: −0.03, −0.01). They also consumed fewer dairy products and meat, and more non-salted oleaginous foods. In addition, women with higher levels of ME consumed more fats and eggs, and fewer processed meat and chocolate based-products, while men consumed more vegetables, whole-grain products, and starches, and less seafood. Regarding macronutrients, individuals with higher levels of ME consumed less protein overall and animal protein, but more plant-based protein. In addition, women with higher ME levels consumed more added fats and omega 3, and less total energy and simple and added carbohydrates, while men consumed more fibers and plant-based lipids. Discussion: ME was associated with a healthier overall diet. These findings suggest that ME could be helpful in the promotion of healthy eating behaviors. Further studies on the dimensions of ME are needed.